Internet Governance Forum Analysis on Artificial Intelligence in Cyber Security - Faishal Ihsan; Nuriyeni Kartika Bintarsari (Insignia: Journal of International Relations, 2021)
Abstract This research examines the way the Internet Governance Forum (IGF) discusses Artificial Intelligence (AI) in the cyber security field. The discussion focuses on 2016, 2017 and 2018 periods. This article utilizes two concepts; cyber politics and internet governance. IGF believes that AI can be regulated collectively with solid frameworks and clear regulations. This in turn will maximize the security aspect of cyber security, which will be cheaper and more efficient in the era of internet freedom and technology rapid development. The paradox in AI lies in the breach of data privacy, which contradicts the goal of cyber security itself, i.e. to protect user’s privacy and sensitive data away from any kind of unauthorized access. Framework cooperation based on mutual recognition of the importance of security within governments, private sectors, technical community and civil society can address privacy and cyber security concerns without undermining the open, free and secure nature of the internet. Hence, a stable and reliable cyber security focused on data protection will provide and preserve trust in cyberspace, and will eventually bring socioeconomic growth, innovation and education advancement. Keywords: IGF, AI, cyber security Abstrak Penelitian ini mengkaji bagaimana Internet Governance Forum (IGF) membahas Artificial Intelligence (AI) di bidang keamanan siber (cyber security). Pembahasan difokuskan pada periode 2016, 2017 dan 2018. Artikel ini menggunakan dua konsep; politik dunia maya (cyberpolitics) dan tata kelola internet (internet governance). IGF memandang bahwa AI dapat diatur secara kolektif melalui kerangka kerja yang kokoh dan regulasi yang jelas. Hal ini pada akhirnya akan memaksimalkan aspek keamanan siber yang semakin murah dan efisien di era kebebasan internet dengan perkembangan teknologi tumbuh pesat. Paradoks dalam AI terletak pada pelanggaran privasi data, yang bertentangan dengan tujuan keamanan dunia maya itu sendiri, yaitu untuk melindungi privasi pengguna dan data sensitif dari segala jenis akses yang tidak sah. Kerangka kerja sama ini didasarkan pada pengakuan timbal balik akan pentingnya keamanan di dalam pemerintah, sektor swasta, komunitas teknis, dan masyarakat sipil yang dapat mengatasi masalah privasi dan keamanan dunia maya tanpa merusak sifat internet yang terbuka, bebas, dan aman. Karenanya, keamanan siber yang stabil, andal dan berfokus pada perlindungan data akan memberikan dan memelihara kepercayaan masyarakat di dunia maya, dan pada akhirnya akan membawa pertumbuhan sosial ekonomi, inovasi, dan kemajuan pendidikan. Keywords: IGF, AI, cyber security